تأثير الري والتسميد العضوي (البقري) في بعض الصفات الخضرية والزهرية لصنف الزيتون "الصوراني" في محافظة حماة (Latakia University Journal -Biological Sciences Series, 2019)
تبين من النتائج الأثر الواضح للري والتسميد العضوي في مقدار الزيادة الكلية في طول النموات الخضرية خلال العامين 2009 و2010 حيث بلغت أعلى قيمة في معاملة الري 300 ليتر / شجرة / رية والتسميد بكمية 20 كغ/شجرة (9.82 سم و12.27 سم) على التوالي. كما حقق الري والتسميد العضوي أثراً واضحاً في متوسط عدد العناقيد الزهرية على الفرع في العام الثاني للتجربة نتيجة التأثير التراكمي لهما، فأرتفع متوسط العدد من 7.99 عنقود /فرع في معاملة الشاهد إلى 13.51 عنقود/فرع في معاملة الري ب 300 ليتر والتسميد 20 كغ/شجرة/سنة, وقد بينت نتائج التحليل الإحصائي تفوق المعاملات كافة على معاملة الشاهد. كما تفوقت معاملات الري بكمية 300 ليتر والتسميد العضوي 20 و30 كغ/شجرة عام 2010 على بقية المعاملات الأخرى في متوسط عدد الأزهار في كل عنقود ولم يكن بينها أي فرق معنوي في العام الثاني للتجربة. وقد بدا واضحاً ارتفاع نسبة الأزهار الخنثى من 18.75% في معاملة الشاهد إلى 48.5% في معاملة الري والتسميد 20 كغ/شجرة/ سنة 2010. أما فيما يتعلق بنسبة العقد فقد تفوقت معاملات الري بكمية 300 ليتر والتسميد العضوي 20 و30 كغ /شجرة على بقية المعاملات الأخرى معنوياً عامي 2009 و2010 ولم يكن بينهما أي فرق معنوي. The results showed the clear influence of irrigation and organic fertilization on the total value for increasing of branches vegetative growth during 2009 – 2010, which gave the highest value for the irrigation treatment 300/ liters/ tree and fertilizing with 20/ kg/ tree (9.82 cm and 12.27 cm respectively). The irrigation and organic fertilization have achieved the clear influence of the average of the number of inflorescence on the branch in the second year because of the accumulative influence for them, in which increased from 7.99 inflorescence/ branch in the control treatment, to 13.51 inflorescence/ branch in the irrigation and organic fertilization with 20 kg/ tree treatment, and the results of the statistics analysis showed a significant all the treatments than the control treatment. The irrigation and organic fertilization with 20 and 30 kg\ tree treatment during 2010 were significantly better than other treatments, and there is not any significantly difference in the average of the flowers number in each inflorescence in the second year. It appears clearly the increase of the flowers sex ratio from 18.75 % in the control treatment to 48.5 % in the irrigation and organic fertilization with 20 kg/ tree treatment during 2010. The irrigation and organic fertilization with 20 and 30 kg\ tree treatment during 2009 and 2010 were significantly better than other treatments in the Fruiting percentage, and there is not any significantly difference between them.